BOTULINUM TOXIN FOR CORRECTION OF GINGIVAL SMILE - Nunes Dantas, Ivanilda; Carolina Marques de Oliveira, Adna; Barros da Cruz Brito, Mayara; de Freitas Lima, Rennaly; Belém Rodrigues Barros Soares, Vinícius; Gomes Moreira, Andréia (Health and Society, 2022)
The gingival smile is an aesthetic concern that affects a large portion of the population, an aesthetically acceptable smile must be harmonious as to the set of teeth, lips and gingival tissue. When the etiological factor is muscle hyperfunction, a treatment option is the application of botulinum toxin type A in the muscles responsible for lifting the upper lip, so the objective of this case report is to demonstrate the use of botulinum toxin to correct gummy smile. . Female patient, age 32, Phototype II, sought care at the Specialization Clinic in Orofacial Harmonization of the IOA-IOP, Campina Grande-PB, due to excessive gingival exposure when smiling. After clinical evaluation, it was observed that the patient had hyperactivity of the levator labii superioris muscles and a gingival exposure of 4 mm. It was proposed to the patient the application of botulinum toxin for the treatment of gummy smile and then the Free and Informed Consent Term was signed specifying all possible complications that could happen, as well as the benefits and results. After the photographs and demarcations, 2 units were applied to the levator labii superioris muscle bilaterally and 2 units to the nasal septum. After 15 days of application, the patient was reassessed, demonstrating an excellent result without excessive exposure of the gingiva and there was no need for a new application. It was concluded that TBA brought a very satisfactory result for the correction of the gummy smile and constitutes a safe and effective treatment.